2017
DOI: 10.22489/cinc.2017.274-197
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Insights from the Finger Tip: How Photoplethysmography Can Help Quantify Sleep

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 10 publications
0
13
1
Order By: Relevance
“…Table 8 compares the performance of our model with the PPG based existing alternatives. From Table 8, it is depicted that our proposed model outperforms over other models listed in the Table except [28] and [29]. In terms of accuracy, [28] outperforms the rest of the models in Table 8.…”
Section: Comparison With Existing Ecg Based Modelsmentioning
confidence: 85%
See 2 more Smart Citations
“…Table 8 compares the performance of our model with the PPG based existing alternatives. From Table 8, it is depicted that our proposed model outperforms over other models listed in the Table except [28] and [29]. In terms of accuracy, [28] outperforms the rest of the models in Table 8.…”
Section: Comparison With Existing Ecg Based Modelsmentioning
confidence: 85%
“…Several studies have reported the use of wearable PPG for sleep-wake classification [24][25][26][27][28][29][30][31]. Since the PPG waveform reflects the blood volume changes at the measuring site on the body, features extracted from PPG contain a wide range of physiological information [32,33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eyal et al [ 33 ] aimed to validate an automated sleep analysis that was based on the inter-beat-interval (IBI) series obtained from transmissive PPG, and that used features of HRV. The algorithm was tested against the gold standard, PSG.…”
Section: Applications Of Photoplethysmography In Clinical Physiological Measurements In Healthy Subjectsmentioning
confidence: 99%
“…Finally, the area under the curve (AUC)-receiver operating characteristics (ROC) curve is a performance measurement for the classification problems at various threshold settings. Eyal et al [33] aimed to validate an automated sleep analysis that was based on the inter-beat-interval (IBI) series obtained from transmissive PPG, and that used features of HRV. The algorithm was tested against the gold standard, PSG.…”
Section: Ppg In Normal Sleepmentioning
confidence: 99%